2013
DOI: 10.1111/jcpe.12170
|View full text |Cite
|
Sign up to set email alerts
|

Role of 3D animation in periodontal patient education: a randomized controlled trial

Abstract: 3D animations are more effective than real-time drawings for periodontal patient education in terms of knowledge recall. 3D animations may be a powerful tool for assisting in the information process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 34 publications
1
52
0
3
Order By: Relevance
“…In their research 93% of the participants found graphic animations helpful. Supporting these findings, Cleeren et al, 12 used 3D animations to explain periodontal conditions, described how patients preferred 3D visualizations to sketches or written instructions. In case of orthognathic surgery, Azem et al, 13 used 2D graphical illustrations of Le Fort I maxillary surgery on a tablet device.…”
Section: Introductionmentioning
confidence: 90%
“…In their research 93% of the participants found graphic animations helpful. Supporting these findings, Cleeren et al, 12 used 3D animations to explain periodontal conditions, described how patients preferred 3D visualizations to sketches or written instructions. In case of orthognathic surgery, Azem et al, 13 used 2D graphical illustrations of Le Fort I maxillary surgery on a tablet device.…”
Section: Introductionmentioning
confidence: 90%
“…This makes it possible for the patients to understand it, eventually allowing them to take responsibility for their own health [14]. Good information and communication increase the patient's possibility to contribute in the decision-making process, leading to higher levels of patient satisfaction, loyalty to the physician and favoring treatment outcomes [14][15][16]. Traditionally, patient-health professional communication in a clinical setting comprises of a face-to-face narrative interaction often combined with static images or real-time sketching (see Figure 5- that patients' comprehension of explanations is often lacking due to the complexity of the medical information [16].…”
Section: Public and Patient Educationmentioning
confidence: 99%
“…Good information and communication increase the patient's possibility to contribute in the decision-making process, leading to higher levels of patient satisfaction, loyalty to the physician and favoring treatment outcomes [14][15][16]. Traditionally, patient-health professional communication in a clinical setting comprises of a face-to-face narrative interaction often combined with static images or real-time sketching (see Figure 5- that patients' comprehension of explanations is often lacking due to the complexity of the medical information [16]. Evidence suggests that patients often do not understand what is being said to them when information is given during a medical encounter due to cultural and educational gaps between clinicians and patients [17].…”
Section: Public and Patient Educationmentioning
confidence: 99%
“…Modern society is based on information technology as the foundation of general social development, contracted, fashionable become modern society people's pursuit of primary fashion, contemporary art elements also shows the current era, with the digital and networked, contemporary art no matter from the aspects of text or image, has extremely high abstractness, the use of symbols is one of the most commonly used in the contemporary art performance, will use the art processing complicated things and abstract into works of art that is the main style of contemporary art [1][2].…”
Section: Introductionmentioning
confidence: 99%